Co-design of on-chip loop antenna and differential class-E power amplifier at 2.4 GHz for biotelemetry applications. (April 2019) - Sunitha, Archana; Manickam, Bhaskar
Abstract: Degradation in gain and efficiency of on-chip antennas limit the communication range of RF transmitters integrated with on-chip antennas below 10 GHz to few centimeters. In this paper, a novel strategy of co-design of fully integrated differential class-E power amplifier and on-chip loop antenna at 2.4 GHz is proposed to increase communication range and save chip area. In the co-design strategy, inductor used for harmonic rejection and matching in the power amplifier is replaced with a parallel capacitance network for harmonic rejection and a modified two turn on-chip loop antenna is used for matching load impedance of power amplifier. From the post-layout simulation results using Cadence Virtuoso, power amplifier has maximum power added efficiency(PAE) of 50.7%, and output power of 17 dBm. On-chip antenna, simulated in Advanced Design System(ADS) has a gain of −19.9 dBi and efficiency of 0.48%. The transmitter designed in UMC 180-nm technology has a higher computed communication range of 1.5 m and is suitable for biotelemetry applications such as patient monitoring.